Prehranjevalne navade in morfološke značilnosti predšolskih otrok v velenjskih vrtcih - Marolt, Mateja; Muhič, Miran; Lahe, Milica (Revija za elementarno izobraževanje, 2011)
Nutritional Habits and the Morphological Characteristics of Preschool Children in Day Care Centres in Velenje. The theoretical part of the article introduces the morphological characteristics of the preschool children, organized sporting activities in Velenje and the influence of food on children’s morphological growth. The purpose of this research is to verify the connection between the nutritional habits and sporting activities of preschool children. The results of our empirical research detail the children’s nutritional habits and the rate of their sporting activity. The data needed for the research was gained in the 2008/09 school year by polling 75 parents whose children attended day-care centers in Velenje. The survey included information on nutritional habits, physical and sporting activity, gender, body weight, height and body mass index. The results show that the majority of children are of normal weight regardless of their gender. The children who were overweight had a higher intake level of sweets than their peers with normal weight. The children who attend organized sporting activities were from the normal weight category.